Solute trapping in rapid solidification. (November 2020) - Pinomaa, Tatu; Laukkanen, Anssi; Provatas, Nikolas
Abstract: Abstract : Rapid solidification gives rise to solute trapping, which decreases solute partitioning and alters equilibrium solidification velocity-undercooling relationships. These effects influence microsegregation, solidification morphology, and the emergent microstructure length scales. Here, we review solute trapping and solute drag in rapid solidification in terms of theory, simulation methods, and experimental techniques. The basic theory to describe solute trapping is contained in the continuous growth model. This model breaks down at high solidification velocities, where solidification transitions abruptly to complete trapping, a limit that can be captured with the local nonequilibrium model. Solute trapping theories contain unknown parameters. Their determination from atomistic simulations or pulsed laser melting experiments is discussed. Microstructural evolution in rapid solidification can be readily investigated with the phase-field method, various alternatives of which are presented here. Uncertainties related to kinetic parameters and heat transfer during rapid solidification can be studied by comparing phase-field simulations to dynamic transmission electron microscopy observations.